2015
DOI: 10.1016/j.molp.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

MYB Transcription Factors as Regulators of Phenylpropanoid Metabolism in Plants

Abstract: Phenylpropanoid-derived compounds represent a diverse family of secondary metabolites that originate from phenylalanine. These compounds have roles in plant growth and development, and in defense against biotic and abiotic stress. Many of these compounds are also beneficial to human health and welfare. V-myb myeloblastosis viral oncogene homolog (MYB) proteins belong to a large family of transcription factors and are key regulators of the synthesis of phenylpropanoid-derived compounds. This review summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
524
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(589 citation statements)
references
References 175 publications
11
524
0
4
Order By: Relevance
“…Of them, the roles of R1 MYB, R2-MYB, R2R3-MYB TFs in regulation of the synthesis of different phenylpropanoid-derived compounds have been extensively studied in many plants such as Arabidopsis, maize, rice, soybean and other plants. 17 In the current analysis, the metabolic genes associated with the reporter metabolites were significantly enriched with putative cis-elements such as MYB-box-like, MYB-box related-like, GARE-like and pyrimidine-box-like associated with the different types of R1MYB, R2MYB and R2R3 MYB in response to both blue and red lights. The enrichment of these elements is supported by the upregulation of Os02g0685200 and Os02g0706400 in blue light, signifying their role in the regulation of the synthesis of different phenolic compounds.…”
Section: Transcriptional Regulation Of Phenolic Compounds Accumulationmentioning
confidence: 62%
“…Of them, the roles of R1 MYB, R2-MYB, R2R3-MYB TFs in regulation of the synthesis of different phenylpropanoid-derived compounds have been extensively studied in many plants such as Arabidopsis, maize, rice, soybean and other plants. 17 In the current analysis, the metabolic genes associated with the reporter metabolites were significantly enriched with putative cis-elements such as MYB-box-like, MYB-box related-like, GARE-like and pyrimidine-box-like associated with the different types of R1MYB, R2MYB and R2R3 MYB in response to both blue and red lights. The enrichment of these elements is supported by the upregulation of Os02g0685200 and Os02g0706400 in blue light, signifying their role in the regulation of the synthesis of different phenolic compounds.…”
Section: Transcriptional Regulation Of Phenolic Compounds Accumulationmentioning
confidence: 62%
“…It is currently established that R2R3-type MYB and basic helix-loop-helix (bHLH) TF families are the most important transcriptional regulators of flavonoid biosynthesis (Xu et al 2015;Liu et al 2015). The transcriptional regulation of anthocyanin and proanthocyanidin biosynthesis has been more extensively studied, and it has been shown that it is mainly exerted by the action of so-called MBW regulation complexes consisting of the R2R3-MYB and bHLH TFs in conjunction with the WD-repeat proteins (WDR).…”
Section: Regulation Of Flavonoid Biosynthesis In Plants: a Comparisonmentioning
confidence: 99%
“…Notably, some genes in the phenolic acid biosynthetic branch (Liu et al, 2015) were also differentially expressed in the Dy mutants ( Fig. 6; Supplemental Table S3A).…”
mentioning
confidence: 98%